Consumption-based carbon intensity of human well-being and its socioeconomic drivers in countries globally. (15th September 2022) - Wang, Jieyu; Wang, Shaojian; Zhou, Chunshan; Feng, Kuishuang
Abstract: The carbon intensity of human well-being (CIWB) is an effective indicator for measuring the progress of the UN Sustainable Development Goals. Compared with production-based accounting, consumption-based CIWB is more useful for the dual tasks of improving cost-effectiveness and increasing equity. Therefore, this study for the first time estimated consumption-based CIWB in 176 countries from 1990 to 2015 by a multi-region input-output model and explored its spatiotemporal patterns. A panel regression technique was adopted to test the impact of the potential socio-economic determinants, with consideration given to the income levels of global countries. We found that global consumption-based CIWB improved annually between 1990 and 2015, and the gap between countries has also gradually decreased since 1995. Apparent differences in consumption-based CIWB and its changes were observed in the four income groups. The lower the income, the more pronounced the trend of consumption-based CIWB reductions was. Economic growth, energy intensity, and exports of goods and services all have a negative impact on the consumption-based CIWB, i.e., elevated CIWB values, while population density, urbanization, renewable energy consumption, and imports of goods and services all lower CIWB values. The effect of socioeconomic factors on consumption-based CIWB also presented different changes depending on income levels. The results of the study provide an important reference for improving the environment while enhancing human well-being. Highlights: A multi-region input-output model was used to calculate consumption-based CIWB. The global consumption-based CIWB decreased from 1990 to 2015, and the differences between countries have narrowed. Significant differences in consumption-based CIWB values and their changes were observed concerning four income groups. We explored the heterogeneity of the effects of socioeconomic factors on consumption-based CIWB at different income levels.